Thermal Degradation-Induced Hydrophobicity and Improved Moisture Resistance of Pyrolyzed Betung Bamboo and Rubberwood Pellets - Ahmad Izzuddin Arrofi; Indra Gumay Febryano; Hendra Prasetia; Wahyu Hidayat (Forest and Nature, 2025)
The increasing global demand for sustainable energy highlights the need for efficient biomass utilization as an alternative to fossil fuels. This study investigates the effect of pyrolysis temperature on the moisture behavior, hydrophobicity, and storage stability of betung bamboo (Dendrocalamus asper) and rubberwood (Hevea brasiliensis) pellets. Pellets were pyrolyzed at 350°C, 400°C, and 450°C for 30 minutes, and their physical properties, including moisture content, water resistance, and water vapor adsorption, were evaluated. Results show that increasing the pyrolysis temperature significantly reduced the moisture content from 9.33% to 1.18% in bamboo pellets and from 10.18% to 1.10% in rubberwood pellets. Pyrolysis enhanced hydrophobicity, as evidenced by stable water vapor adsorption below 5% over 14 days, compared to more than 15% in untreated pellets. Pyrolyzed pellets also exhibited superior water resistance, retaining their structural integrity after 24 hours of immersion, whereas the control samples deformed completely. These improvements enhance storage stability, minimize the risk of self-ignition, and increase combustion efficiency by reducing water-related energy losses. The findings demonstrate that optimizing pyrolysis temperature effectively improves pellet quality, offering a promising approach for sustainable bioenergy production from forest-based biomass resources.